Optimization of a photopolymerizable material based on a photocyclic initiating system using holographic recording - Ibrahim, A. (2012)
A set of photoinitiating systems (PIS) for free radical photopolymerization was studied using time-resolved spectroscopic experiments, real-time FTIR and holographic recording. It is shown that the efficiency of the photoinitiating system can be drastically increased when a redox additive is added to the conventional dye/coinitiator system by virtue of photocyclic behaviour. The homogeneous photopolymerization process was found to reach a fast vitrification, limiting the conversion at about 55%. By contrast, holographic recording underlines the differences in photoinitiating system reactivity, allowing diffraction efficiencies close to unity for the most reactive PIS.